Grief, ecocritical negativity, and the queer anti-pastoral. Issue 2 (3rd April 2019) - Clark, Cameron
ABSTRACT: This article introduces the queer anti-pastoral as an ecocinematic model that destabilizes pastoral conventions of nature as a site for harmonious patterns and generative transformations at the service of the human. I analyze queer anti-pastoral films such as Calvaire, Twentynine Palms, and Criminal Lovers for how they offer useful strategies to rethink the terms of the social and the environmental by traversing their very negations and subsequent transformations. Central to this inquiry is grief and the ways in which its narrative and affective-aesthetic arrangements dovetail into injurious acts of misrecognition, misplacement, and substitution. By pairing together Eugenie Brinkema's affective formalism with Leo Bersani's aesthetic theories, I ultimately argue that grief in the queer anti-pastoral provides an ecological ethics and environmental politics of detachment. This, in turn, prompts new modes of environmental consciousness and impersonal relationality that are not entirely founded on empathy or care, but on what opens up when ecological interdependency fails.